PENGARUH RETURN ON EQUITY, CAPITAL ADEQUACY RATIO DAN RETURN ON ASSETS TERHADAP RETURN SAHAM PADA PT BANK RAKYAT INDONESIA (PERSERO) Tbk PERIODE 2014-2023 - Hasan, Aulia; Hendra, Dede (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the effect of Return On Equity, Capital Adequacy Ratio and Return On Assets on the PT Bank Rakyat Indonesia Tbk. in period 2014-2023. The method used in the research is a quantitative method by taking stocks data as well as financial report data of PT Bank Rakyat Indonesia Tbk. The data analysis used is descriptive statistic analysis, multiple linear regression analysis, classic assumption test and hypothesis test. The research results show that partially Return On Equity has no effect on stocks return because the significant value is 0,143 > 0,05 and tstatistic 1,622 < ttable 2,22814, partially Capital Adequacy Ratio has no effect on stocks return because the significant value is 0,517 > 0,05 and tstatistic -0,678 < ttable 2,22814, partially Return On Asset has no effect on stocks return because the significant value is 0,162 > 0,05 and tstatistic 1,542 < ttable 2,22814. Based on simultaneous test, Return On Equity, Capital Adequacy Ratio and Return On Assets have no effect on Stock Returns because the significant value is 0,523 > 0,05 and tstatistic 0,833 < Ftable 5,32.